Urban self-development of a Palestinian refugee camp in Jerusalem - Haneya, Halima Abu (Africana Studia, 2022)
This paper examines how indigenous people are self-developed and how they reproduce their space to overcome their precariousness. It focuses on the refugees of Shu’fat Camp in Jerusalem, who were able to fulfil their growing need for housing and provide accommodation for other Jerusalemites, seeking affordable housing to maintain their residency status in their city. This is done by tracing the self-urban practices of the Shu’fat Camp refugees as forms of unorganized collective action. Specifically, this research investigates the power strategies of the indigenous people in order to control changes in their own lives. The data in this paper comes from dozens of semi-structured interviews in the camp. The research uses settler colonialism as a general analytical framework and relies on Lila Abu Lughod’s (1990) analysis of power and resistance and Asef Bayat’s (2013) concept of “social non-movements.” The research emphasizes Shu’fat residents as active people of agency and not only victims or passive recipients of Israel’s policies and measures imposed on them. Keywords: Settler colonialism, urban self-developments, Shu’fat refugee camp, social non-movements.